DDGS (Distillers Dried Grains With Solubles) as an ingredient in feed of the nile tilapia - Lewandowski, Vanessa; Sary, Cesar; Pessini, Jhonis Ernzen; Boscolo, Wilson; Bittencourt, Fábio; Feiden, Aldi (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">The aim of the present study was to evaluate the potential utilization of DDGS on diet of Nile Tilapia by chemical and digestibility analyses. Firstly, the chemical composition of the ingredient was evaluated and then were made two diets: a reference one and a test diet made of 80% with the reference diet and 20% with DDGS, for the digestibility study. For the faeces collection was used the indirect method, using chromium oxide as an inert marker. After the collection, the faeces were destined to chemical composion analysis and so the experimental diets. With the results, the Nile Tilapia coefficient of digestibility of the DDGS nutrients was calculated. Proteins and total lipids mainly compose the DDGS, which gives its high concentration of crude energy. The Nile Tilapia has the capacity of using, mainly protein, with digestibility coeficients of 89.51% when compared to energy, which is 62.52%. Therefore, this ingredient shows potential to be utilized on diets of Nile tilapia as a proteic ingredient.